Clinical importance of the Mandalay spitting cobra (Naja mandalayensis) in Upper Myanmar – Bites, envenoming and ophthalmia. (September 2020) - Sai-Sein-Lin-Oo,; Myat-Thet-Nwe,; Khin-Maung-Gyi,; Than-Aye,; Mi-Mi-Khine,; Myat-Myat-Thein,; Myo-Thant,; Pyae-Phyo-Aung,; Oakkar-Kyaw-Khant,; Aye-Zarchi-San,; Du-Wun-Moe,; Htay-Aung,; et al.
Abstract: Examination of 18 cobras brought to three hospitals in the Mandalay Region by patients bitten or spat at by them distinguished 3 monocled cobras ( Naja kaouthia ) and 15 Mandalay spitting cobras ( N. mandalayensis ), based on their morphological characteristics. We confirm and extend the known distributions and habitats of both N. mandalayensis and N. kaouthia in Upper Myanmar. Clinical symptoms of local and systemic envenoming by N . mandalayensis are described for the first time. These included local swelling, blistering and necrosis and life-threatening systemic neurotoxicity. More information is needed about the clinical phenotype and management of bites by N . mandalayensis, the commoner of the two cobras in Upper Myanmar. Since the current cobra antivenom manufactured in Myanmar has lower pre-clinical efficacy against N. mandalayensis than N. kaouthia, there is a need for more specific antivenom therapy. Highlights: The Mandalay spitting cobra ( Naja mandalayensis ) is much more common that the monocle cobra ( N. kaouthia ) in Upper Myanmar. Injuries caused by spitting of venom and bites were admitted to three hospitals in Mandalay Division. The known distribution of both species of cobra is extended. Naja mandalayensis envenoming causes neurotoxicity as well as local tissue damage. The only available cobra antivenom in Myanmar may not be adequate for treating envenoming by N. mandalayensis .